2023
DOI: 10.1128/spectrum.04437-22
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Ceftazidime-Avibactam, Ceftolozane-Tazobactam, Cefiderocol, and Novel Darobactin Analogs against Multidrug-Resistant Pseudomonas aeruginosa Isolates from Pediatric and Adolescent Cystic Fibrosis Patients

Abstract: Antimicrobial resistance (AMR) represents an ever increasing threat to the health care system. Even recently licensed drugs are often not efficient for the treatment of infections caused by Gram-negative bacteria, like Pseudomonas aeruginosa , a causative agent of lung infections. To address this unmet medical need, innovative antibiotics, which possess a new mode of action, need to be developed. Here, the antibiogram of clinical isolates derived from cystic fibrosis patients was genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…In about half of the cases (n=44, 51%), the studies lacked a clear definition or citation of the method for interpreting trailing (broth microdilution) or colonies within zone (disk diffusion). There were 14 data sets for which a method other than broth microdilution was used (n=9 disk diffusion [8,36,37,51,65,72,75,88,92,95], n=5 gradient strip [36,68,69,94,97]). Apotransferrin for medium preparation was reported on 4 data sets (2 studies [60,61]).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…In about half of the cases (n=44, 51%), the studies lacked a clear definition or citation of the method for interpreting trailing (broth microdilution) or colonies within zone (disk diffusion). There were 14 data sets for which a method other than broth microdilution was used (n=9 disk diffusion [8,36,37,51,65,72,75,88,92,95], n=5 gradient strip [36,68,69,94,97]). Apotransferrin for medium preparation was reported on 4 data sets (2 studies [60,61]).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…infections, limiting the treatment options of Cefiderocol [ 116 ]. Different studies are ongoing to explore the efficacy of possible combinations with other antimicrobials [ 117 , 118 ].…”
Section: Antimicrobial Strategies Involving Iron Metabolismmentioning
confidence: 99%
“…baumannii), or Klebsiella pneumoniae (K. pneumoniae), against which many other antibiotics are not effective anymore. ,,,, Two derivatization series of darobactins published by Groß et al and Seyfert et al have confirmed the efficacy of scaffold modification by biotechnological engineering of the fully synthetic darobactin biosynthetic gene cluster (BGC) to enhance the bioactivity of analogues, , which was partly confirmed by the study of Marner et al The feasibility of modifications at specific positions of the core peptide was a prerequisite for analyzing their influence on antibacterial activity and for understanding how analogues of this novel compound class interact with its unique target BamA. These new insights together with the first described cocrystal structure of darobactin A ( DA ) and BamA helped establishing the structure–activity relationships of the different derivatives. , The earlier derivatization series increased the antibacterial activity of darobactins up to 128-fold for darobactin 22 ( D22 ) compared to native DA , even against clinical isolates of carbapenem-resistant A.…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, the risk of cross-resistance is lower, and they are proven to exhibit an auspicious broad-spectrum Gram-negative activity against clinically relevant and multiresistant pathogens such as Pseudomonas aeruginosa (P. aeruginosa), Escherichia coli (E. coli), Acinetobacter baumannii (A. baumannii), or Klebsiella pneumoniae (K. pneumoniae), against which many other antibiotics are not effective anymore. 11,12,15,19,20 Two derivatization series of darobactins published by Groß et al and Seyfert et al have confirmed the efficacy of scaffold modification by biotechnological engineering of the fully synthetic darobactin biosynthetic gene cluster (BGC) to enhance the bioactivity of analogues, 12,15 which was partly confirmed by the study of Marner et al 21 The feasibility of modifications at specific positions of the core peptide was a prerequisite for analyzing their influence on antibacterial activity and for understanding how analogues of this novel compound class interact with its unique target BamA. These new insights together with the first described cocrystal structure of darobactin A (DA) and BamA helped establishing the structure−activity relationships of the different derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation